Established Population of the Gulf Coast Tick, Amblyomma maculatum (Acari: Ixodidae), Infected with Rickettsia parkeri (Rickettsiales: Rickettsiaceae), in Connecticut. Issue 3 (18th January 2021) - Molaei, Goudarz; Little, Eliza A H; Khalil, Noelle; Ayres, Bryan N; Nicholson, William L; Paddock, Christopher D
Abstract: We identified an established population of the Gulf Coast tick ( Amblyomma maculatum Koch) infected with Rickettsia parkeri in Connecticut, representing the northernmost range limit of this medically relevant tick species. Our finding highlights the importance of tick surveillance and public health challenges posed by geographic expansion of tick vectors and their pathogens.